A Comparison of Foramen Magnum Measurements between Male and Female in Autopsy Cases Performed in the Mortuary of a Tertiary Care Hospital in Western Maharashtra - Dhokia Gautamkumar R.; Radhakrishna K.V.; Rathee Abhishek; Sarala M.; D.K. Shivakumar; Manral Ishita (Indian Journal of Forensic Medicine and Pathology, 2025)
Context: The identi𿿿cation of the deceased is essential to the forensic investigationand Sex is one of the most important characteristics that may be used to determine identity. The characteristics of the foramen magnum, according to research, are useful in determining gender. Aims: To compare Foramen Magnum measurements between Male and Female in autopsy cases. Settings and Design: This study is a Cross sectional analytical study was conducted at the medicolegal center of a Tertiary Care Hospital of Western Maharashtra. Methods and Material: The study used a sample of 90 autopsy cases (45 males and 45 females) from the mortuary of a tertiary care hospital in Western Maharashtra, India. The sagittal and transverse diameters of the foramen magnum were measured using a divider and sliding vernier calliper. Results: The results of the study showed that the transverse diameter of the foramen magnum was signi𿿿cantly larger in males than females (p<0.0001), while there was no signi𿿿cant difference in the sagittal diameter betweenthetwogenders (p = 0.11).Conclusions: The study concludes that the transverse diameter of the foramen magnum is a useful parameter for sex determination in forensic investigations.